Intermedin Inhibits the Ox-LDL–Induced Inflammation in RAW264.7 Cells by Affecting Fatty Acid–Binding Protein 4 Through the PKA Pathway - Liu, Kai; Shi, Rufeng; Wang, Si; Liu, Qi; Zhang, Hengyu; Chen, Xiaoping (Frontiers in Pharmacology, 2021)
Objectives: Macrophages stimulated by oxidized low-density lipoprotein (ox-LDL) play an important role in the occurrence and progression of atherosclerosis. Fatty acid–binding protein 4 (FABP4), mainly existing in macrophages and adipocytes, can influence lipid metabolism and inflammation regulated by macrophages. Herein, we first established the connection between intermedin (IMD: a new peptide that has versatile biological activities in the cardiovascular system) and FABP4 and then investigated the influence of IMD on ox-LDL-induced changes in RAW264.7 macrophages line. Methods: The bioinformatics analysis, such as gene ontology enrichment and protein–protein interactions, was performed. For ox-LDL–stimulated assays, RAW264.7 was first pretreated with IMD and then exposed to ox-LDL. To explore the cell signaling pathways of IMD on inflammatory inhibition, main signaling molecules were tested and then cells were co-incubated with relevant inhibitors, and then exposed/not exposed to IMD. Finally, cells were treated with ox-LDL. The protein and gene expression of FABP4, IL-6, and TNF-α were quantified by WB/ELISA and RT-qPCR. Results: In the ox-LDL-stimulated assays, exposure of the RAW264.7 macrophages line to ox-LDL reduced cell viability and increased the expression of FABP4, as well as induced the release of IL-6 and TNF-α (all p < 0.05). On the other hand, IMD prevented ox-LDL–induced cell toxicity, FABP4 expression, and the inflammatory level in RAW264.7 (all p < 0.05) in a dose-dependent manner. The inhibition of FABP4 and the anti-inflammatory effect of IMD were partially suppressed by the protein kinase A (PKA) inhibitor H-89. Conclusion: IMD can prevent ox-LDL–induced macrophage inflammation by inhibiting FABP4, whose signaling might partially occur via the PKA pathway.